Digital humans : thriving in an online world - Ashcroft, Paul (Entrepreneur); Jones, Garrick, 1965- (John Wiley & Sons, Inc., 2022)
"We are all digital humans now. What does this mean for how we live and how we work? How do digital humans thrive in a connected world? Life and work today is a connected mass of networks, people and technology. This connected world is so complex and fast evolving it can be considered alive. In this provocative and insightful book, Paul Ashcroft and Garrick Jones shine a light on how to activate organizations so that they can transform themselves -- and what digital means for people who work within them. This new book brings together knowledge from a wide range of disciplines including complexity theory, anthropology, history and behavioural science combined with the latest thinking on organisational transformation. It highlights principles (such as algorithms, self-organisation, pattern recognition) that underpin the success of digital organisations based on our twenty years of helping organisations making the shift to digital and our learnings through the pandemic in the accelerated shift to hybrid, digital working. In Digital Humans the authors describe the importance of keeping humans at the centre of the digital age -- and understanding our place within these new digital eco-systems. It provides cases and principles for how to shift to digital and adapt to the new hybrid reality across strategy and decision making, transformation and capability building. The book describes how to transform organisations whilst keeping humans at the centre of the digital age. It is practical, inspiring and engaging -- with stories from some of the largest global organisations to some of the smallest using the most innovative ideas."--